2002
DOI: 10.1183/09031936.02.00282002
|View full text |Cite
|
Sign up to set email alerts
|

Response to hypoxia of pulmonary arteries in chronic obstructive pulmonary disease: anin vitrostudy

Abstract: Response to hypoxia of pulmonary arteries in chronic obstructive pulmonary disease: an in vitro study. V.I. Peinado, S. Santos, J. Ramírez, J. Roca, R. Rodriguez-Roisin, J.A. Barberà. #ERS Journals Ltd 2002. ABSTRACT: Patients with chronic obstructive pulmonary disease (COPD) show impaired hypoxic pulmonary vasoconstriction that might contribute to abnormal gas exchange and could be related to endothelial dysfunction in pulmonary arteries. The aim of the study was to investigate the response of PA to hypoxic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 28 publications
3
21
0
Order By: Relevance
“…Diseases exposing lungs to chronic hypoxia such as chronic obstructive pulmonary disease are known to both contribute to the development of pulmonary hypertension in humans (7) and to be associated with a loss of the HPV response, which maintains ventilation to perfusion ratios (25). The results of this study detected evidence that increased extracellular hydrogen peroxide could be a factor in how chronic hypoxia can promote an impairment of HPV under conditions where pulmonary hypertension develops.…”
Section: Perspectives and Significancesupporting
confidence: 49%
See 1 more Smart Citation
“…Diseases exposing lungs to chronic hypoxia such as chronic obstructive pulmonary disease are known to both contribute to the development of pulmonary hypertension in humans (7) and to be associated with a loss of the HPV response, which maintains ventilation to perfusion ratios (25). The results of this study detected evidence that increased extracellular hydrogen peroxide could be a factor in how chronic hypoxia can promote an impairment of HPV under conditions where pulmonary hypertension develops.…”
Section: Perspectives and Significancesupporting
confidence: 49%
“…A loss of the hypoxic pulmonary vasoconstriction (HPV) response which maintains ventilation to perfusion ratios is seen in humans with chronic obstructive pulmonary disease (COPD) and in pulmonary arteries isolated from these individuals (25). Studies in animal models of chronic hypoxia have provided evidence for processes that are associated with increased generation of reactive oxygen species (ROS) from sources, including various Nox oxidases participating in the progression of hypoxia-induced pulmonary hypertension development (10,12,13,15,19,21,23).…”
mentioning
confidence: 99%
“…Indeed, hypoxic pulmonary vasoconstriction is less active in patients with severe structural impairment of pulmonary muscular arteries [14]. Furthermore, in isolated pulmonary artery rings, it has been recently shown that the magnitude of contraction induced by hypoxic stimulus is inversely related to the endothelial function and directly related to the arterial PO 2 [41]. These findings suggest that the impairment of endothelial function is associated with an altered response to hypoxic stimulus that further worsens gas exchange.…”
Section: Hypoxic Pulmonary Vasoconstrictionmentioning
confidence: 73%
“…At this stage, the reactivity of pulmonary arteries to hypoxia might also be altered in some patients with mild COPD [16,34,41], hence contributing to alveolar ventilation/perfusion ratio (V9A/Q9) mismatching and promoting the development of arterial hypoxaemia. In this scenario, sustained exposure to hypoxaemia may induce further pulmonary vascular remodelling thus amplifying the initial effects of cigarette-smoke products ( fig.…”
Section: Mechanisms Of Pulmonary Vascular Changesmentioning
confidence: 99%
“…The group has focused its activity on the cellular and molecular mechanisms of pulmonary vascular abnormalities associated with COPD. The major achievements of the group have been as follows: 1) demonstration that changes in pulmonary arteries occur at early stages [2,3]; 2) characterisation of the cellular and molecular changes in pulmonary arteries [4]; 3) implication of cigarette smoking in the pathogenesis of pulmonary vascular abnormalities through an inflammatory mechanism [5]; 4) impact of endothelial dysfunction on the vascular response to hypoxia and gas exchange regulation [6]; 5) characterisation of mediators that contribute to vascular remodelling [7]; and 6) identification of vascular progenitor cells in the intima of pulmonary arteries from patients with COPD [1]. The group takes part in the European Union-funded Integrated Project PULMOTENSION.…”
Section: My Research As Part Of My Working Group/ Research Teammentioning
confidence: 99%